Adenoviral Transduction of Dickkopf-1 Alleviates Silica-Induced Silicosis Development in Lungs of Mice - Cai, Qian; Ma, Jia; Wang, Jing; Wang, Juying; Cui, Jieda; Wu, Shuang; Wang, Zhaojun; Wang, Na; Wang, Jiaqi; Yang, Dandan; Yang, Jiali; Xue, Jing; et al. (Human gene therapy, 2022)
Silicosis is an occupational disease caused by inhalation of silica dust, which is hallmarked by progressive pulmonary fibrosis associated with poor prognosis. Wnt/β-catenin signaling is implicated in the development of fibrosis and is a therapeutic target for fibrotic diseases. Previous clinical studies of patients with pneumoconiosis, including silicosis, revealed an increased concentration of circulating WNT3A and DKK1 proteins and inflammatory cells in bronchoalveolar lavage compared with healthy subjects. The present study evaluated the effects of adenovirus-mediated transduction of ( ), a Wnt/β-catenin signaling inhibitor, on the development of pulmonary silicosis in mice. Consistent with previous human clinical studies, our experimental studies in mice demonstrated an aberrant Wnt/β-catenin signaling activity coinciding with increased Wnt3a and Dkk1 proteins and inflammation in lungs of silica-induced silicosis mice compared with controls. Intratracheal delivery of adenovirus expressing murine Dkk1 (AdDkk1) inhibited Wnt/β-catenin activity in mouse lungs. The adenovirus-mediated gene transduction demonstrated the potential to prevent silicosis development and ameliorate silica-induced lung fibrogenesis in mice, accompanied by the reduced expression of epithelia--mesenchymal transition markers and deposition of extracellular matrix proteins compared with mice treated with "null" adenoviral vector. Mechanistically, AdDkk1 is able to attenuate the lung silicosis by inhibiting a silica-induced spike in TGF-β/Smad signaling. In addition, the forced expression of Dkk1 suppressed silica-induced epithelial cell proliferation in polarized human bronchial epithelial cells. This study provides insight into the underlying role of Wnt/β-catenin signaling in promoting the pathogenesis of silicosis and is proof-of-concept that targeting Wnt/β-catenin signaling by gene transduction may be an alternative approach in the prevention and treatment of silicosis lung disease.